2019
DOI: 10.1038/s41598-018-37567-7
|View full text |Cite
|
Sign up to set email alerts
|

A search for tiny dragons (Dracunculus medinensis third-stage larvae) in aquatic animals in Chad, Africa

Abstract: Dracunculus medinensis, or human Guinea worm (GW), causes a painful and debilitating infection. The global Guinea Worm Eradication Program (GWEP) has successfully reduced human GW cases from 3.5 million in 21 countries in 1986 to only 30 cases in three remaining countries in 2017. Since 2012, an increase in GW infections in domestic dogs, cats and baboons has been reported. Because these infections have not followed classical GW epidemiological patterns resulting from water-borne transmission, it has been hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 17 publications
(32 reference statements)
0
44
0
Order By: Relevance
“…[Lithobates] catesbeiana) are susceptible to infection with D. insignis (Crichton and Beverly-Burton 1977;Eberhard and Brandt, 1995;Eberhard et al, 2014). Despite these experimental data, a published report has documented a single frog in Chad that was found infected with D. medinensis (Eberhard et al, 2016a), and similar findings in 2 additional frog species in Chad have been documented (Cleveland et al, 2019.). Our finding of D. insignis L3s in 11 frogs provides support that paratenic hosts may be involved in the life cycle of Dracunculus spp.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…[Lithobates] catesbeiana) are susceptible to infection with D. insignis (Crichton and Beverly-Burton 1977;Eberhard and Brandt, 1995;Eberhard et al, 2014). Despite these experimental data, a published report has documented a single frog in Chad that was found infected with D. medinensis (Eberhard et al, 2016a), and similar findings in 2 additional frog species in Chad have been documented (Cleveland et al, 2019.). Our finding of D. insignis L3s in 11 frogs provides support that paratenic hosts may be involved in the life cycle of Dracunculus spp.…”
Section: Discussionmentioning
confidence: 55%
“…Each animal was euthanized via cervical dislocation, identified to species, eviscerated, and skinned. The remaining muscle tissue was bluntly dissected, facilitating release and recovery of any D. insignis larvae present as described previously (Eberhard et al 2016a(Eberhard et al , 2016bCleveland et al, 2019). Tissue was placed in Petri dishes with Dulbecco's phosphate buffered saline (DPBS) for a minimum of 4 hr until microscopy was conducted for larval detection (Eberhard and Brandt, 1995).…”
Section: Animal Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, despite our small sample size, our data indicate that dogs can ingest relatively few copepods while drinking, but there are still many factors to investigate to determine the primary transmission route(s) of D. medinensis in the remaining GWD-endemic countries. Other possibilities include ingestion of amphibian paratenic hosts or fish transport hosts 2,[4][5][6]15 . Currently, there are many interventions in place to minimize transmission risk including: tethering of infected dogs, treatment of potentially contaminated water bodies with Abate ® , and the burning or burial of fish entrails, but dog infections continue to occur suggesting that improved adherence to interventions or new interventions are necessary to interrupt transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In Chad, there are limited numbers of human infections despite the significant increase in the number of infected domestic dogs and domestic cats, suggesting alternative transmission pathways may be involved in some animal infections 2,3 . Recent data indicates that amphibians can be paratenic hosts and fish can be transport hosts, possibly contributing to this unusual epidemiology [4][5][6] . Two recent genomic studies showed that the D. medinensis derived from humans and animals are the same species and part of the same population of worms 7,8 .…”
mentioning
confidence: 99%